The Effect of Brand Image and Brand Trust on Oppo Cellphones Purchasing Decisions In Banjar City - Yogi Sugiarto Maulana; Mela Marista (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2021)
This study aimed to determine and analyze the brand image, brand trust, and the magnitude of these variables influence on purchasing decisions in Banjar City. The research approach used is a quantitative approach with explanatory methods—sampling using simple random sampling technique, with 89 respondents. The statistical method used in this study is multiple linear regression. The analysis results show that the brand image variable is in a good category (valid and reliable). The brand trust variable is in the adequate category, and the purchase decision is in a good category. Obtained the magnitude of the simultaneous influence of brand image and brand trust on purchase decisions in Banjar City is 31.2%. The magnitude of the partial effect of brand image on purchase decisions is 22.56%, the magnitude of the partial influence of brand trust on purchase decisions is 21.62%. The simultaneous hypothesis testing results state that there is a significant effect of brand image and brand trust on purchase decisions Oppo in Banjar City.